SNP genotyping for fast and consistent clustering of maize inbred lines into heterotic groups - Oliveira,Lander Santos de (2021)
Abstract Advances in genotyping technologies have transformed the way breeding programs manage their genetic resources. The identification of single nucleotide polymorphisms (SNPs) can improve understanding of the genetic diversity of maize (Zea mays) inbred lines and their classification into heterotic groups, which is useful in determining certain crosses to obtain hybrids with higher yield performance. The genetic diversity of 293 inbred lines was investigated with 5252 SNPs with minor allele frequency (MAF)>5%. There was an average of 525 SNPs per chromosome. Polymorphism information content (PIC) averaged 0.297. The unweighted pair group method with arithmetic mean analysis (UPGMA) and principal component analysis (PCA) based on the genetic distance matrix revealed four similar clusters and high cophenetic correlation coefficients (0.953 and 0.863, respectively). The results showed consistency between genetic distance-based grouping and the heterotic groups previously established using pedigree and topcross information for the inbred lines studied.